Evidence Summary of Pruritus Management in Patients With Atopic Dermatitis: Implications for Nursing Practice - Yuzhen Shen; Qian Shen; Manni Chen; Rufang Liu (Journal of Cosmetic Dermatology, 2026)
ABSTRACT Background To synthesize the most current and relevant evidence regarding pruritus management in patients with atopic dermatitis (AD), and to identify implications for nursing assessment, education, monitoring, and follow‐up. Method An extensive literature search was conducted across multiple databases, including the Cochrane Library, Embase, and PubMed in English, as well as Chinese databases such as WanFang Data and CNKI. The search encompassed publications from the inception of these databases up to December 2024. Results A total of 26 publications were ultimately included in the analysis. These consisted of 14 randomized controlled trials, 3 systematic reviews, 2 cohort studies, 1 scoping review, 2 observational studies, 1 case report, 1 expert opinion, and 4 expert consensus documents. The findings were organized into physician‐directed therapies, nursing‐implemented or nursing‐supported interventions, and nursing‐specific practice implications; region‐specific or traditional therapies were presented separately because of their limited international generalizability. Key implications for nursing practice were identified in the areas of symptom assessment, skin barrier care, patient education, treatment adherence, safety monitoring, and follow‐up support. Nurses play an important supportive role in implementing physician‐directed therapies and non‐pharmacological interventions while also promoting adherence and long‐term disease management. Conclusion Evidence‐based management of pruritus in atopic dermatitis requires integration of pharmacological and non‐pharmacological strategies. Nursing practice contributes substantially through symptom assessment, patient education, skin care support, adherence promotion, safety monitoring, and follow‐up, thereby helping improve pruritus control and quality of life.